Voices Of Patients: An Evaluation Of Satisfaction With Nursing And Healthcare Assistant Care In Saudi Arabia (The Review of Diabetic Studies, 2024)
Background: Patient satisfaction has become a central performance indicator in modern health-care systems, and nursing care is consistently identified as one of the strongest determinants of overall patient experience. Moreover, patient satisfaction with nursing and healthcare assistant (HCA) care is an important quality indicator. Aim: This study aimed to evaluate patients’ satisfaction with the quality of nursing care provided in a regional hospital in Saudi Arabia and to examine the influence of selected demographic characteristics on satisfaction. Methods: A cross-sectional, descriptive-correlational design was employed. A total of 300 patients admitted to medical, surgical, and obstetrics/gynecology units were recruited. Data were collected using a validated Arabic version of the Patient Satisfaction Questionnaire, assessing six dimensions of nursing care: patient care orientation, communication, teaching, reassurance, professionalism, availability/attentiveness, and admission/discharge processes. Descriptive statistics summarized satisfaction levels, and Kruskal–Wallis and chi-square tests examined associations with demographic variables. Results: Overall, 86% of patients reported satisfaction with nursing care. The highest satisfaction was observed in professionalism, cultural respect, and responsiveness to call bells (agreement ≥92%). Communication (especially in Arabic), pre-admission instructions, and information about physician availability received the lowest satisfaction ratings. Significant differences in overall satisfaction were observed according to educational level (χ² = 4.2, p = 0.02) and number of hospital admissions (χ² = 5.9, p = 0.03), while age, gender, and marital status showed no significant associations. Item-level analysis indicated that gender influenced perception of cultural respect, friendliness, plan-of-care explanations, pre-admission instructions, and timely receipt of discharge medications. Conclusion: Patients generally reported high satisfaction with nursing care; however, communication barriers, information provision, and physician availability were identified as areas for improvement. Addressing language barriers, enhancing pre-admission and discharge education, and ensuring staff availability can further improve patient satisfaction. These findings have important implications for nursing leadership, hospital administrators, and policymakers in Saudi Arabia to optimize the quality of nursing care.